1999
DOI: 10.1128/jvi.73.12.9827-9831.1999
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Role of Epstein-Barr Virus-Encoded RNAs in Burkitt’s Lymphoma Cell Line Akata

Abstract: Our previous reports indicated that Epstein-Barr virus (EBV) contributes to the malignant phenotype and resistance to apoptosis in Burkitt’s lymphoma (BL) cell line Akata (N. Shimizu, A. Tanabe-Tochikura, Y. Kuroiwa, and K. Takada, J. Virol. 68:6069–6073, 1994; J. Komano, M. Sugiura, and K. Takada, J. Virol. 72:9150–9156, 1998). Here we report that the EBV-encoded small RNAs (EBERs) are responsible for these phenotypes. Transfection of the EBER genes into EBV-negative Akata clones restored the capacity for gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(72 citation statements)
references
References 30 publications
1
67
0
1
Order By: Relevance
“…The ability of L22 to reverse the inhibition by EBER-1 of the dsRNA-mediated activation of PKR, has several implications. Recent reports have shown that high-level expression of EBER-1 can lead to the resistance of cells to physiological stresses and pro-apoptotic stimuli, can confer aspects of the transformed phenotype, and may result in outright tumorigenicity in some cases [9][10][11][12]. There is evidence to suggest that these effects are at least partially a consequence of the ability of the RNA to block the activation of PKR (which is strongly pro-apoptotic) [53][54][55][56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…The ability of L22 to reverse the inhibition by EBER-1 of the dsRNA-mediated activation of PKR, has several implications. Recent reports have shown that high-level expression of EBER-1 can lead to the resistance of cells to physiological stresses and pro-apoptotic stimuli, can confer aspects of the transformed phenotype, and may result in outright tumorigenicity in some cases [9][10][11][12]. There is evidence to suggest that these effects are at least partially a consequence of the ability of the RNA to block the activation of PKR (which is strongly pro-apoptotic) [53][54][55][56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…3,26 The function of EBER RNAs is less clear; EBER expression is not required for B-cell transformation, 27 but recent studies suggest that EBER RNAs may play some role in oncogenesis. 28,29 Analysis of case 31 indicates that continued expression of EBER transcripts is not necessary for maintenance of the transformed phenotype in HRS cells. Although expression of EBER RNAs is generally considered a hallmark of latent EBV infection, lack of EBER expression has been described in EBV-associated hepatocellular carcinoma and EBV PCR-positive breast cancers.…”
Section: Case 31mentioning
confidence: 99%
“…Os EBER também se ligam à proteino-quinase ativada por RNA fita dupla (PKR), uma quinase que atua inativando o fator de iniciação de síntese protéica eIF-2, em função de estímulos antivirais de interferon (IFN) a e b. Tais efeitos variam desde inibição temporária da síntese protéica da célula hospedeira até apoptose. 47 A inserção dos genes EBER em linhagens de células Akata (de linfoma de Burkitt) EBV-negativas revelou que eles são responsáveis pela restituição da tumorigenicidade em camundongos SCID, crescimento em agar semi-sólido, resistência a estímulos apoptóticos e pelo aumento na expressão de BCL-2 48 . Tem sido demonstrado que os EBER podem induzir a expressão de interleucina-10 (IL-10) em linhagens de linfoma de Burkitt, sugerindo que os referidos transcritos virais possam promover uma supressão do sistema imune do hospedeiro mediada por IL-10 44 .…”
Section: Eber1 E Eber2unclassified